Long non-coding RNA CASC2 regulates osteoblasts matrix mineralization - Freitas, Jaime; Moura, Sara Reis; Barbosa, Mário Adolfo; Santos, Susana G.; Almeida, Maria Inês (Frontiers in Bioengineering and Biotechnology, 2023)
Long non-coding RNAs (lncRNAs) are master regulators of gene expression and have recently emerged as potential innovative therapeutic targets. The deregulation of lncRNA expression patterns has been associated with age-related and noncommunicable diseases, including osteoporosis and bone tumors. However, the specific role of lncRNAs in physiological or pathological conditions in the bone tissue still needs to be further clarified, for their exploitation as therapeutic tools. In the present study, we evaluate the potential of the lncRNA CASC2 as a regulator of osteogenic differentiation and mineralization. Results show that CASC2 expression is decreased during osteogenic differentiation of human bone marrow-derived Mesenchymal Stem/Stromal cells (hMSCs). CASC2 knockdown, using small interfering RNA against CASC2 (siCASC2), increases the expression of the late osteogenic marker Bone Sialoprotein (BSP), but does not impact ALP staining level nor the expression of early osteogenic transcripts, including RUNX2 and OPG. Although siCASC2 does not impact hMSC proliferation nor apoptosis, it promotes the mineralization of hMSC cultured under osteogenic-inducing conditions, as shown by the increase of calcium deposits. Mass spectrometry-based proteomic analysis revealed that 89 proteins are regulated by CASC2 at late osteogenic stages, including proteins associated with bone diseases or anthropometric and musculoskeletal traits. Specifically, the Cartilage Oligomeric Matrix Protein (COMP) is highly enhanced by CASC2 knockdown at late stages of osteogenic differentiation, at both transcriptional and protein level. Inhibition of COMP impairs osteoblasts mineralization as well as the expression of BSP levels. The results indicate that lncRNA CASC2 regulates late osteogenesis and mineralization in hMSC via COMP and BSP. In conclusion, this study suggests lncRNA CASC2 as a potential new therapeutic target in bone mineralization.